2005
DOI: 10.1111/j.1365-201x.2005.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic aerobic exercise enhances components of the classical and novel insulin signalling cascades in Sprague–Dawley rat skeletal muscle

Abstract: Collectively, these findings suggest that chronic aerobic exercise enhances components of both the classical and novel insulin signalling cascades in normal rodent skeletal muscle, which may contribute to an increased insulin-stimulated plasma membrane GLUT4 protein concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 51 publications
(146 reference statements)
2
22
2
Order By: Relevance
“…However, studies have demonstrated alterations of this pathway in rodent skeletal muscle in response to high-fat feeding [21], monosodium glutamate treatment [25], streptozotocin treatment [26], and exercise [4,16]. In the present investigation, we report no difference in the plasma membrane concentration of c-Cbl, CAP, or flotillin among sedentary lean and obese Zucker rats after insulin stimulation.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…However, studies have demonstrated alterations of this pathway in rodent skeletal muscle in response to high-fat feeding [21], monosodium glutamate treatment [25], streptozotocin treatment [26], and exercise [4,16]. In the present investigation, we report no difference in the plasma membrane concentration of c-Cbl, CAP, or flotillin among sedentary lean and obese Zucker rats after insulin stimulation.…”
Section: Discussioncontrasting
confidence: 61%
“…In contrast, insulin-stimulated TC10 protein concentration was not decreased in high-fat-fed Sprague-Dawley rats [16]. These differences could be attributed to the model of skeletal insulin resistance used.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations